Pengaruh Capital Adequacy Ratio (CAR) Dan Aktiva Produktif Terhadap Profitabilitas Pada Sektor Perbankan Yang Terdaftar Di Bursa Efek Indonesia - Panjaitan B11108075, Ridwan Gifson (Jurnal Manajemen Update, 2014)
As a financial institution that collects funds from the public in the form of deposits, the bank also has a role in the provision of loans to customers for financing activities, investments or working capital. This loan is a loan that can be counted as interest income from lending. The measurement of banking capacity to get income from loan interest is in the form of Net Interest Margin (NIM). NIM performance can be influenced by many factors, in this research the factors that will be tested are Capital Adequacy Ratio (CAR) and Aktiva Produktif atas Total Aktiva (APTA). This research aimed to analyze whether capital performance (Capital Adequacy Ratio) and Earning Assets (Aktiva Produktif atas Total Aktiva) simultaneously and partially influence Net Interest Margin (NIM) or not. The samples were taken by using purposive judgement sampling so that five years research period can be obtained. The period was begun from 2006 until 2011 and covered thirdteen banks go public at Indonesia Stoke Exchange. The data is then analyzed by using multiple linear regressions which previously had undergone the classical assumption test. Through this research linearity test shows that there is only one independent variable has a linear relationship, namely the Capital Adequacy Ratio (CAR). So that the regression analysis using simple linear regression. Apakah terjemahan ini lebih baik daripada yang awal? Kirim Terima kasih atas kirimannya. Please help Google Translate improve quality for your language here. The regression result shows that Capital Adequacy Ratio (CAR) is simultaneously influence to Net Interest Margin (NIM). That it’s also about partially influence analyze, CAR is partially influence to Net Interest Margin (NIM). The correlation between independent variable (CAR) with dependent variable (NIM) is strong enough. Independent variable can explain the changes in NIM of 20.9% while the rest can be explained by other variables which are not tested in this research. Keywords: Capital Adequacy Ratio (CAR), Aktiva Produktif atas Total Aktiva (APTA) and Net Interest Margin (NIM)